Exploring Information Credibility in Traditional Media Websites and News Portals - Çipuri, Ramadan; Nelku, Raimonda; Erbas, Isa (Calitatea Vieții, 2025)
Digital media transmits information faster than traditional media, but it is often met with skepticism regarding its credibility. As digital media becomes increasingly dominant, it is crucial to assess the credibility of its information. This paper presents a study that evaluates the credibility of information on traditional media websites and news portals among journalism and communication university students. A survey of 253 students from seven different journalism and communication departments examines factors influencing media credibility, including medium dependency, interactivity, transparency, argument strength, personal expertise, and information quality. The study employs various machine learning models to validate its findings, showing that traditional media websites are perceived as more credible than news portals, with argument strength and information quality being the most significant contributors to the credibility of information.